Penerapan Kaidah Fikih Dar’u al-Mafāsid Aulā min Jalbi al-Maṣaliḥ terhadap Penggunaan Kadaver sebagai Media Pembelajaran pada Pendidikan Kedokteran: The Application of the Fiqh Principle of Dar’u al-Mafāsid Aulā min Jalbi al-Maṣāliḥ Regarding the Use of Cadavers as a Learning Medium in Medical Eduction (AL-FIKRAH: Jurnal Kajian Islam, 2025)
This study explores the application of the Islamic legal maxim dar’u al-Mafāsid aulā min jalbi al-Maṣāliḥ (preventing harm takes precedence over securing benefit) in the use of cadavers for medical education. It aims to assess the ethical balance between benefits and harms based on Islamic legal principles. Using a qualitative-normative method with a deductive approach, the research analyzes classical and contemporary Islamic jurisprudence through textual and comparative analysis, and applies the takhrīj al-Furū‘ ‘alā al-Uṣūl method. Findings show that cadaver use provides significant benefits across three levels of maqāṣid al-Syarī‘ah: at the ḍarūrīyāt (essential) level, it supports life preservation (ḥifẓ al-Nafs) by improving medical competence; at the ḥājīyāt (complementary) level, it enhances learning effectiveness; and at the taḥsīnīyāt (refinement) level, it supports surgical innovation. Harms include violations of corpse dignity, burial delays, chemical use, psychological effects, and potential religious-cultural sensitivities. The study concludes that the maxim’s application is not absolute and must be contextually analyzed within the ijtihādī domain. Since the benefits are definitive (qaṭ'ī), broad (kulliyyah), and essential (ḍarūrīyāt), they outweigh the speculative and limited harms. Cadaver use is permissible if obtained legally and ethically, treated with dignity, and supplemented with alternative methods. Use of non-Muslim cadavers is also acceptable under ethical guidelines. This study contributes theoretically to Islamic legal methodology and practically to the development of ethical policies in medical education.